2023
DOI: 10.1136/jnnp-2022-330619
|View full text |Cite
|
Sign up to set email alerts
|

Plasma biomarkers for Alzheimer’s disease: a field-test in a memory clinic

Abstract: BackgroundThe key Alzheimer’s disease (AD) biomarkers are traditionally measured with techniques/exams that are either expensive (amyloid-positron emission tomography (PET) and tau-PET), invasive (cerebrospinal fluid Aβ42and p-tau181), or poorly specific (atrophy on MRI and hypometabolism on fluorodeoxyglucose-PET). Recently developed plasma biomarkers could significantly enhance the efficiency of the diagnostic pathway in memory clinics and improve patient care. This study aimed to: (1) confirm the correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 36 publications
(72 reference statements)
0
20
0
Order By: Relevance
“…However, we require real-world blood biomarker data before validating them for clinical use. 5 6 To this end, here, we present three papers that illuminate the practical application of blood biomarkers-Altomare et al 7 (Geneva Cohort) and Lehman et al 8 (BALTAZAR cohort) assess the performance of AD blood biomarkers in memory clinics, and Veria et al 9 highlight potential for positive AD blood biomarkers in amyotrophic sclerosis.…”
Section: Blood Biomarkers: Ready For Clinical Practice?mentioning
confidence: 99%
“…However, we require real-world blood biomarker data before validating them for clinical use. 5 6 To this end, here, we present three papers that illuminate the practical application of blood biomarkers-Altomare et al 7 (Geneva Cohort) and Lehman et al 8 (BALTAZAR cohort) assess the performance of AD blood biomarkers in memory clinics, and Veria et al 9 highlight potential for positive AD blood biomarkers in amyotrophic sclerosis.…”
Section: Blood Biomarkers: Ready For Clinical Practice?mentioning
confidence: 99%
“…Blood-based biomarkers might likely be more useful during the earliest stages, where phospho-tau can predict future increases in tau-PET 66,67 and can play a key role in prescreening subjects for further neuroimaging examinations. 68 In this context, the use of plasma as a gateway to traditional biomarkers could avoid additional investigations in relevant proportions of cases, making the diagnostic workup more cost-effective and improving patient care. 68 There are some limitations and strengths to this study.…”
Section: Discussionmentioning
confidence: 99%
“…68 In this context, the use of plasma as a gateway to traditional biomarkers could avoid additional investigations in relevant proportions of cases, making the diagnostic workup more cost-effective and improving patient care. 68 There are some limitations and strengths to this study. First, we used MMSE as a measure of cognitive decline, although we are aware that MMSE is a global measure characterized by a ceiling effect, less sensitive than other tests or test combinations.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical utility will also need to be established; the plasma biomarker test will need to have a positive impact on patient management to secure future reimbursement and wide‐scale adoption. In a field‐test study conducted in a memory clinic, plasma biomarkers demonstrated excellent diagnostic accuracy compared to current confirmatory diagnostic tests (MRI, PET, and CSF biomarker analysis); it was estimated that plasma biomarker testing reduced the number of confirmatory diagnostic tests needed by up to 49%, highlighting their potential clinical utility as diagnostic tools 72 …”
Section: Clinical Implementation Of Plasma Biomarker Testing In the A...mentioning
confidence: 99%
“…In a field-test study conducted in a memory clinic, plasma biomarkers demonstrated excellent diagnostic accuracy compared to current confirmatory diagnostic tests (MRI, PET, and CSF biomarker analysis); it was estimated that plasma biomarker testing reduced the number of confirmatory diagnostic tests needed by up to 49%, highlighting their potential clinical utility as diagnostic tools. 72 Implementation studies should be undertaken to gather evidence on how plasma biomarker testing can be incorporated in various different clinics and contexts and to examine the most effective ways to use plasma biomarker testing in clinical settings. The expectation is that this will vary depending on the type of clinic and the standard of care within the clinic or geographical region in question but more research is needed.…”
Section: Clinical Implementation Of Plasma Biomarker Testing In the A...mentioning
confidence: 99%